2012
DOI: 10.4161/cbt.13.4.18877
|View full text |Cite
|
Sign up to set email alerts
|

OSU-03012 suppresses GRP78/BiP expression that causes PERK-dependent increases in tumor cell killing

Abstract: We have further defined mechanism(s) by which the drug OSU-03012 (OSU) kills tumor cells. OSU lethality was suppressed by knock down of PERK and enhanced by knock down of ATF6 and IRE1α. OSU treatment suppressed expression of the chaperone, BiP/GRP78, and did so through reduced stability of the protein. Knock down of BiP/GRP78 further enhanced OSU lethality. Overexpression of BiP/GRP78 abolished OSU toxicity. Pre-treatment of cells with OSU enhanced radiosensitivity to a greater extent than concomitant or sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 32 publications
4
77
0
Order By: Relevance
“…Antibody reagents, other kinase inhibitors, caspase inhibitors cell culture reagents, and non-commercial recombinant adenoviruses have been previously described. [39][40][41][42] Previously characterized semi-established GBM5 / GBM6 / GBM12 / GBM14 glioblastoma cells were supplied by Dr. C.D. James (University of California, San Francisco) and Dr. J.N.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibody reagents, other kinase inhibitors, caspase inhibitors cell culture reagents, and non-commercial recombinant adenoviruses have been previously described. [39][40][41][42] Previously characterized semi-established GBM5 / GBM6 / GBM12 / GBM14 glioblastoma cells were supplied by Dr. C.D. James (University of California, San Francisco) and Dr. J.N.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were isolated at the indicated times and SDS PAGE and immunoblotting was performed as described in refs. [39][40][41][42] Blots were observed by using an Odyssey IR imaging system (LI-COR Biosciences, Lincoln, NE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug was inferred to treat glioblastomas also according to [180]. See Section 5.6 on the PERK-eIF2α-ATF4-CHOP apoptotic signaling machinery for details, according to authors' review opinion.…”
Section: Targeting Hsp90 Alonementioning
confidence: 99%
“…Initially, it was thought that the mechanism of action of AR-12 was the direct inhibition of PDK-I (30), which results in lower AKT phosphorylation, along with endoplasmic reticulum stress and autophagy induction (24,26,31). However, recent studies indicate that PDK-I is not the target of AR-12 (26,32); rather, the target is immunoglobulin heavy chain-binding protein (GRP78/ BiP). Additionally, our previous studies indicated that AR-12 induces autophagy in macrophages at 1 M (28, 29), which is much lower than the concentration observed for its inhibitory activity against PDK-1.…”
mentioning
confidence: 99%